Groundwater Monitoring to Support Development of BMPs for Groundwater Protection: The Abbotsford‐Sumas Aquifer Case Study. Issue 1 (10th February 2015) - Zebarth, Bernie J.; Ryan, M. Cathryn; Graham, Gwyn; Forge, Thomas A.; Neilsen, Denise
Abstract: The Abbotsford‐Sumas Aquifer is arguably the most studied case in Canada of groundwater nitrate contamination associated with agricultural production. Underlying some of the most productive agricultural land in Canada, this highly vulnerable trans‐boundary aquifer provides a unique case study on the opportunities and challenges of addressing water quality issues. A groundwater monitoring program initiated in the early 1990s has been important in tracking spatial and temporal variation in groundwater nitrate concentration. However, small land parcels with spatially and temporally variable land use and management practices and sub‐horizontal flow in this highly permeable sand and gravel aquifer make it difficult to relate groundwater monitoring results to specific agricultural practices. Other approaches pointed to the historical over‐application of N relative to crop requirement (primarily as manure used to increase soil organic matter during replanting but also as a nutrient source during production). Despite changes in agricultural practices, and programs aimed at raising grower awareness, no appreciable change in average groundwater nitrate concentration has occurred over the monitoring period. On individual land parcels, nitrate contamination may be reduced through development and adoption of an integrated suite of beneficial management practices (BMPs) to improve N fertilization, irrigation and alley vegetation management, and in particular to eliminate application of any organic soil amendment such as untreated manure in which the N has not been stabilized (e.g., by composting). However, the substantial N imbalance on a regional scale, and the lack of an effective on‐going consultative process among stakeholders, remain major barriers to the development, demonstration and adoption of BMPs.